Chitinase (CHI) of Spodoptera frugiperda affects molting development by regulating the metabolism of chitin and trehalose - Liu, Xiang-Yu; Wang, Sha-Sha; Zhong, Fan; Zhou, Min; Jiang, Xin-Yi; Cheng, Yi-Sha; Dan, Yi-Hao; Hu, Gao; Li, Can; Tang, Bin; Wu, Yan (Frontiers in Physiology, 2022)
Chitin is the main component of insect exoskeleton and midgut peritrophic membrane. Insect molting is the result of the balance and coordination of chitin synthesis and degradation in chitin metabolism under the action of hormones. In this study, a 678 bp dsRNA fragment was designed and synthesized according to the known CHI (Chitinase) sequence of Spodoptera frugiperda. It was injected into the larvae to observe the molting and development of S. frugiperda. At the same time, the activities of trehalase and chitinase, the contents of trehalose, chitin and other substances were detected, and the expression of related genes in the chitin synthesis pathway was determined. The results showed that CHI gene was highly expressed at the end of each instar, prepupa and pupal stage before molting; At 12 and 24 h after dsRNA injection of CHI gene of S. frugiperda, the expression of CHI gene decreased significantly, and the chitinase activity decreased significantly from 12 to 48 h. The expression of chitin synthase (CHSB) gene decreased significantly, and the chitin content increased significantly. Some larvae could not molt normally and complete development, leading to certain mortality. Secondly, after RNAi of CHI gene, the content of glucose and glycogen increased first and then decreased, while the content of trehalose decreased significantly or showed a downward trend. The activities of the two types of trehalase and the expression levels of trehalase genes decreased first and then increased, especially the trehalase activities increased significantly at 48 h after dsCHI injection. And trehalose-6-phosphate synthase (TPS), glutamine: fructose-6-phosphate amidotransferase (GFAT), UDP-N-acetylglucosamine pyrophosphorylases (UAP), hexokinase (HK), glucose-6-phosphate isomerase (G6PI) and phosphoacetylglucosamine mutase (PAGM) all decreased significantly at 24 h, and then increased or significantly increased at 48 h. These results indicated that when the expression of chitinase gene of S. frugiperda was inhibited, it affected the degradation of chitin in the old epidermis and the formation of new epidermis, and the content of chitin increased, which led to the failure of larvae to molt normally. Moreover, the chitin synthesis pathway and trehalose metabolism were also regulated. The relevant results provide a theoretical basis for screening target genes and developing green insecticides to control pests by using the chitin metabolism pathway.